Digital Literacy and Student Creativity Through E-Resources on the Quality of Learning in College - Endang Herawan; Yopi Nisa Febianti; Alifa Lesta Safitri (Journal of Education Technology, 2023)
Student skills and the quality of learning in tertiary institutions are determined by the activities and creativity of lecturers in motivating student learning. In improving students' skills in the field of learning technology, students need to improve their skills. The purpose of this study is to improve students' ability regarding digital literacy and student creativity in utilizing e-resources to improve the quality of student learning. In this study using descriptive research method through quantitative approach. The determination of samples using purposive sampling, sampling is calculated using lameshow formula so as to get 96 research samples. Then the data collection using questionnaires that are shared through social media, as well as data supported by interview results. The data analysis in this study used associative data analysis, which is a multiple linear regression using the help of SPSS for windows v.25. Furthermore, the results of the data analysis are interpreted into sentences as explanatory. The results of the analysis in this study showed there is an influence between digital literacy and student creativity in utilizing e-resources to improve the quality of learning in universities indicating a moderate correlation. The correlation is shown by the existence of independent learning activities conducted by students in finding learning materials used in teaching and learning activities in universities.